KONSTRUKSI MAKNA PENYANDANG FILARIASIS - Purwanti Hadisiwi (Indonesian Journal of Dialectics, 2011)
The existence of persons with filariasis become public attention since the news release of nine persons who presumably died after participating in mass medical treatment at the end of 2009. Persons with filariasis who experience swelling in some part of his body, through self-disclosure of their sickness, disabilities, the meaning of medication, the meaning of filariasis risk information, the meaning of mass medical treatment and self-concept become the objectives of this study.  This study used qualitative method through phenomenological approach. Informants were selected purposively based on age, gender, type of disability, stage of disability and location of their living. The data was collected through in-depth interviews and participatory observation. The results show that self-meaning which has been affected by sex and initial age of illness had defined the sufferers as person with resignation, person in despair, never-surrender person and person with no illness. Furthermore, persons with filariasis interpreted their disability as self-humiliating, needs to be pitied, but in some cases even as a driving spirit. Most people with filariasis had not sought treatment anymore because of the undertaken medical treatments had been perceived as too procedural, expensive and frustrating. Meanwhile, the traditional treatments were perceived by some persons with filariasis as being hopeless. Linear, inaccurate and dishonest risk information from the doctor and news exaggeration by mass media has been perceived by some as reliable, but mostly frightening and confusing. Mass medical treatments had developed a more positive self-concept for most people with filariasis, but not for few others that remained to be negative.